Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Hasil Belajar Matematika Materi Kaidah Pencacahan Bagi Siswa Kelas XII IPA 2 SMAN 1 Nunukan Selatan Tahun Pelajaran 2021/2022 - Sulastri Sulastri (Continuous Education: Journal of Science and Research, 2022)
This classroom action research aims to 1) Describe the process of learning mathematics material on enumeration rules for students of class XII IPA 2 SMAN 1 Nunukan Selatan by using the application of jigsaw type cooperative learning. 2) Describe the increase in learning outcomes of mathematics material on enumeration rules for students of class XII IPA 2 SMAN 1 Nunukan Selatan with the application of jigsaw cooperative learning. This study uses the classroom action research phase which includes planning, action, observation, and reflection which is carried out in two cycles. Data collection techniques in this study were through observation of the learning process and tests. Data analysis was carried out by processing data from observations of the learning process and learning outcomes data in a qualitative and quantitative descriptive way. The results of the research show that the learning process is getting better. Successively obtained an average learning process in Cycle I of 64.31%, and Cycle II of 79.99%. In terms of learning outcomes, the number of students who achieved a passing score in Cycle I was 50% and in Cycle II was 94%. In general, it can be concluded that up to Cycle II there was an increase in the process and results of students' mathematics learning in the enumeration rule material through jigsaw cooperative learning.